(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the trend of changes in quality of life (QoL), assessed using the OQLQ score, in patients with class III skeletal deformity treated with the orthodontics-first approach (OFA) and the surgery-first approach (SFA). Methods: A retrospective study enrolled 40 patients (OFA n = 20, SFA n = 20). The OFA group was assessed at four timepoints: before orthodontic treatment (T0), immediately before surgery (T1), 3 months post-surgery (T2), and 6 months post-surgery (T3). The SFA group was assessed at T1, T2, and T3. Results: Both groups were comparable in age, sex, and baseline cephalometric parameters (p > 0.05). OFA group total OQLQ increased from 34.12 ± 11.05 at T0 to 48.23 ± 12.34 at T1. At T1, the OFA group had a significantly higher total OQLQ score than the SFA group (48.23 ± 12.34 vs. 33.23 ± 10.32; p < 0.001). At T2 and T3, scores decreased significantly in both groups with no significant between-group differences (p > 0.05). Conclusion: Both the conventional orthodontics-first approach (OFA) and the surgery-first approach (SFA) yielded outcomes in restoring long-term quality of life in patients with skeletal Class III deformities. However, SFA demonstrated a distinct clinical advantage by shortening the waiting period and eliminating the phase of psychological distress associated with presurgical orthodontic decompensation.